Recent Advances in Stimuli-Sensitive Amphiphilic Polymer-Paclitaxel Prodrugs - Zhou, Man; Wen, Lijuan; Wang, Cui; Lei, Qiao; Li, Yongxiu; Yi, Xiaoqing (Frontiers in Bioengineering and Biotechnology, 2022)
Paclitaxel (PTX) is a broad-spectrum chemotherapy drug employed in the treatment of a variety of tumors. However, the clinical applications of PTX are limited by its poor water solubility. Adjuvants are widely used to overcome this issue. However, these adjuvants often have side effects and poor biodistribution. The smart drug delivery system is a promising strategy for the improvement of solubility, permeability, and stability of drugs, and can promote sustained controlled release, increasing therapeutic efficacy and reducing side effects. Polymeric prodrugs show great advantages for drug delivery due to their high drug loading and stability. There has been some groundbreaking work in the development of PTX-based stimulus-sensitive polymeric prodrug micelles, which is summarized in this study. We consider these in terms of the four main types of stimulus (pH, reduction, enzyme, and reactive oxygen species (ROS)). The design, synthesis, and biomedical applications of stimulus-responsive polymeric prodrugs of PTX are reviewed, and the current research results and future directions of the field are summarized.